Aleatoric Democracy - Bruno S. Frey; Margit Osterloh (Center for Economic Studies and ifo Institute (CESifo), 2016)
Democracy usually is identified by the right to vote. However, in recent times voting procedures have been criticized, as they seemingly do not guarantee that all parts of the population have an adequate voice in the established political process. We suggest invigorating an old but nearly forgotten procedure to overcome this deficit: Aleatoric Democracy based on a combination of voting and random decisions. By using random mechanisms the interests of the whole population are considered. Persons and ideas, being so far disregarded, are taken into account. Democracy becomes vivid and creative, and does not run the danger of being entrenched.
Keywords: B10; D70; D78; H10; N40; 330; democracy; right to vote; lot; random; aleatoric; silent majority